1986
DOI: 10.1037/0882-7974.1.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Relation of age at onset to duration of episode in unipolar depression.

Abstract: The purpose of this study was to test the hypothesis that the duration of episodes of unipolar depression increases with age at onset. On the basis of elevated scores on a self-report depression measure, 2,020 persons were selected from a larger community sample to be interviewed and diagnosed using the Schedule for Affective Disorders and Schizophrenia-Research Diagnostic Criteria procedures. Of the 2,020 persons, 865 had a history of one or more episodes of unipolar depression. The potential effects of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In addition to the heterogeneity regarding cognitive functioning and medical illness, several studies have found that age at onset of the first depressive episode may differentiate depressive subtypes. Women with a previous history of depression are more likely than men with such histories to have recurrent episodes, but duration of depressive episodes does not appear to vary according to age at onset (Lewinsohn et al, 1986). Late-onset depressives have a lower incidence of family history of depression, longer hospital stay, more residual symptoms at discharge from the hospital (Conwell et al, 1989), and higher frequency of medical comorbidity (Alexopoulos et al, 1993a).…”
Section: Heterogeneity Of Geriatric Depressionmentioning
confidence: 99%
“…In addition to the heterogeneity regarding cognitive functioning and medical illness, several studies have found that age at onset of the first depressive episode may differentiate depressive subtypes. Women with a previous history of depression are more likely than men with such histories to have recurrent episodes, but duration of depressive episodes does not appear to vary according to age at onset (Lewinsohn et al, 1986). Late-onset depressives have a lower incidence of family history of depression, longer hospital stay, more residual symptoms at discharge from the hospital (Conwell et al, 1989), and higher frequency of medical comorbidity (Alexopoulos et al, 1993a).…”
Section: Heterogeneity Of Geriatric Depressionmentioning
confidence: 99%
“…Women with a previous history of depression are more likely than men with such histories to have recurrent episodes, but duration of depressive episodes does not appear to vary according to age at onset (Lewinsohn et al, 1986). Women with a previous history of depression are more likely than men with such histories to have recurrent episodes, but duration of depressive episodes does not appear to vary according to age at onset (Lewinsohn et al, 1986).…”
Section: Heterogeneity Of Geriatric Depressionmentioning
confidence: 85%
“…Depression in the elderly is different from depression in younger persons when the onset is after age 60, with evidence that there are more psychotic or delusional symptoms, more symptoms of hypochondriasis, and less evidence of a family history of affective disorder (Lewinsohn, Fenn, Stanton, & Franklin, 1986;Lewinsohn, Rohde, Seeley, & Fischer, 1991). Up until the early 1970s, there is a tendency for depressive symptoms to decline in the elderly, but the symptoms then gradually increase and are associated with greater life stress, less social support, decreased social interaction and social skill, engagement in fewer activities that the elder enjoys, and higher levels of depressive thoughts.…”
Section: Literature Reviewmentioning
confidence: 98%